2017
DOI: 10.2116/analsci.33.1013
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetophoretic Micro-convection around a Droplet in a Capillary

Abstract: The electromagnetophoretic behavior of organic droplets in an electrolyte solution was investigated in a silica capillary cell using a superconducting bulk magnet (3.5 T) and a magnetic circuit (2.7 T). The initially dispersed emulsion droplets of dodecane migrated to the wall of the capillary, responding to the direction of an electric current, and coalesced to form smaller and larger droplets after some repeated migrations. When the electric current was applied continuously, the larger droplets became arrang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Funaki et al observed a curious micro-convection of smaller organic droplets around a larger organic droplet in a capillary electromagnetophoretic system. 241 When the electric current of 0.5 or 1.0 mA was applied at 3.5 T or 2.7 T, larger droplets became arranged at regular intervals on the capillary wall, and smaller droplets circulated around the larger droplets (Fig. 17).…”
Section: Lab On a Chip Critical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Funaki et al observed a curious micro-convection of smaller organic droplets around a larger organic droplet in a capillary electromagnetophoretic system. 241 When the electric current of 0.5 or 1.0 mA was applied at 3.5 T or 2.7 T, larger droplets became arranged at regular intervals on the capillary wall, and smaller droplets circulated around the larger droplets (Fig. 17).…”
Section: Lab On a Chip Critical Reviewmentioning
confidence: 99%
“…The electromagnetophoretic buoyancy was shown to be useful for dynamic force measurement and manipulation of diamagnetic particles. 244 The local Lorentz force, which can be changed by the inhomogeneous current density around micro-subjects, 241,254 will be useful to fabricate micro-structured flow systems. In a Cu magnetoelectrodeposition surface, its chiral selectivity was observed.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Recent analytical studies of emulsions include evaluations of collapse processes, , analysis of the interface of droplets, and analysis of emulsion products . Turbidity measured by ultraviolet–visible spectrophotometry (UV–vis) has normally been used for the evaluation of emulsion stability. For instance, the time profile of turbidity was studied to evaluate the coalescence and/or solubilization kinetics of oil in microemulsion droplets , and for determining the phase-inversion temperature. , However, when an incident light insufficiently passes through an emulsion with rather high turbidity, it is difficult to obtain reliable data.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, information on the reaction dynamics and thermodynamics can be deduced from the particle behavior in a physical field. Suwa and Watarai studied the magnetophoresis of various particles and evaluated the interfacial adsorption of laurate complexes with dysprosium ions on fluorotoluene microdroplets from their magnetophoretic velocities . The surface complexation between laurate and the paramagnetic dysprosium ion largely modifies the magnetic property of the microdroplet and allows detection of the reaction that occurs on the droplet.…”
mentioning
confidence: 99%